1988
DOI: 10.3758/bf03208711
|View full text |Cite
|
Sign up to set email alerts
|

A response-selection basis for the mixed-category, repeated-stimulus inferiority effect

Abstract: When subjects identify a target stimulus with an assigned keypress response, flanking noise stimuli produce interference if they signal an alternative response and slight facilitation if they are identical to the target. However, when the possible stimuli come from two distinct categories Getters and digits), interference also occurs if the noise letters are identical to the target. Four experiments were conducted to determine whether this mixed-category, repeated-stimulus inferiority effect is due to stimulus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…All this implies that the PRE in our study and the PRE reported in the triad study are qualitatively different: The former arises in early vision whereas the latter arises from a rapid accrual of noise information whose effect on target processing is definitely at the decision level. Recently, Proctor and Fober (1988) obtained the NRE in a triad presentation of stimuli from two different categories, digits and letters, but this NRE disappeared when response assignment was categorically determined. This and other results led those authors to claim response selection as the locus of the NRE.…”
Section: Discussionmentioning
confidence: 99%
“…All this implies that the PRE in our study and the PRE reported in the triad study are qualitatively different: The former arises in early vision whereas the latter arises from a rapid accrual of noise information whose effect on target processing is definitely at the decision level. Recently, Proctor and Fober (1988) obtained the NRE in a triad presentation of stimuli from two different categories, digits and letters, but this NRE disappeared when response assignment was categorically determined. This and other results led those authors to claim response selection as the locus of the NRE.…”
Section: Discussionmentioning
confidence: 99%
“…The feature-specific inhibition model (Bjork & Murray, 1977) is also an unlikely candidate because RB has been found to occur when C I and C2 are separated by several distractor items with long ISIs (Kanwisher, 1987;Park & Kanwisher, 1994). The model has also been questioned on the basis of other findings, such as the mixed-category, repeated-stimulus inferiority effect (see, e.g., Egeth & Santee, 1981;Proctor & Fober, 1988) obtained when two stimuli are not physically identical. For example, Egeth and Santee showed that RB (which they call the repeatedletter inferiority effect) occurred even when the two letters were visually dissimilar and shared only the same name (e.g., Aa).…”
Section: Methodsmentioning
confidence: 99%
“…For example, when a target letter is flanked in irrelevant locations by instances of a letter from the same set, responses typicaIly are faster when the flanker and target identities correspond in terms of the response that each indicates than when they do not (see, e.g., Eriksen & Eriksen, 1974). This effect, known as the Eriksen flanker effect, has been shown to persist with little change in magnitude across four sessions of approximately 300 trials each (Proctor & Fober, 1988). Also, the Stroop effect for color naming, in which naming of the ink color ofa form is slowed when the form speIls an irrelevant color word, has been shown to decrease with practice but not to disappear (see, e.g., Clawson et aI., 1995;Stroop, 1935Stroop, /1992, as has a version of the Stroop effect in which reading location words (left, right, up, down) was slowed when they were printed inside irrelevant arrows that pointed in conflicting directions (Shor, Hatch, Hudson, Landrigan, & Shaffer, 1972).…”
Section: Reduction and Persistence Of The Simon Effect With Practicementioning
confidence: 98%